2008
DOI: 10.2337/dc07-2374
|View full text |Cite
|
Sign up to set email alerts
|

A New Zealand Linkage Study Examining the Associations Between A1C Concentration and Mortality

Abstract: OBJECTIVE -To examine associations between A1C concentration and mortality in a New Zealand population. (1999 -2001), participants were offered A1C testing. The participants were anonymously linked to the national mortality collection to 31 December 2004. Hazard ratios (HRs) and 95% CIs adjusted for age, ethnicity, smoking, and sex were estimated using Cox regression. RESEARCH DESIGN AND METHODS -During a HepatitisFoundation screening campaign for hepatitis BRESULTS -There were 47,904 participants (71% Mâori, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 21 publications
9
54
3
Order By: Relevance
“…Several studies reported a consistent graded relationship between HbA 1c and both all-cause mortality [16,18,37,38] and fatal and/or non-fatal CVD [16,18]. In contrast, Selvin et al [7] found that the risk of coronary heart disease only increased above an HbA 1c of 4.6%.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies reported a consistent graded relationship between HbA 1c and both all-cause mortality [16,18,37,38] and fatal and/or non-fatal CVD [16,18]. In contrast, Selvin et al [7] found that the risk of coronary heart disease only increased above an HbA 1c of 4.6%.…”
Section: Discussionmentioning
confidence: 96%
“…There is broad evidence for hyperglycaemia as a risk factor for cardiovascular disease [15,16], extended very recently by results of a large collaborative meta-analysis of 102 studies on fasting glucose concentrations [17], but data on the low range of glycaemia are inconsistent. In addition to the ARIC study and NHANES, four earlier studies reported mortality risk for categories of glycated haemoglobin in non-diabetic populations, with one study suggesting a potentially increased risk [8] and three studies suggesting no increased risk with low levels of glycated haemoglobin [6,7,9]. However, low numbers of events, particularly in the low range of glycated haemoglobin (below~5.0%), limit an accurate risk estimation in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies examining the association of glycated haemoglobin with all-cause mortality in nondiabetic populations have had limited statistical power to test the nature of the association at the low end of the distribution [6][7][8][9]. Therefore, in order to test the shape of association and explore potential underlying mechanisms, we analysed the association of glycated haemoglobin with all-cause and cause-specific mortality in men and women in a UK population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that HbA 1c is a risk factor for all-cause mortality in individuals with no prior diagnosis of diabetes [4][5][6][7][8]. In stepwise screening for type 2 diabetes mellitus, HbA 1c is often measured.…”
Section: Introductionmentioning
confidence: 99%